Survey on request form content and result reporting in therapeutic drug monitoring service among laboratories in Czechia and Slovakia - Šálek, Tomáš (Array, 2020)
Introduction: The aim of the study was to investigate current practice and policies of therapeutic drug monitoring (TDM) service requesting and result reporting in Czechia and Slovakia. Materials and methods: All 149 laboratories that measure plasma drug concentrations were given an online questionnaire during a regular external quality assessment TDM cycle. The questionnaire consisted of 17 questions. The optimal TDM practice was defined as the application of all elements (age, body weight, time of sampling, date of the first administration, time of the last dose administration, the dose, the dosing interval, the route of administration, information on reason of testing, and information on other co–administered drugs) needed for reporting a recommendation for further drug dosing (positive response to question number 16). Results: The response rate was 69%, 103 out of 149 laboratories measuring drug concentrations. Only 12% (12 out of 103 laboratories) of the laboratories implemented all elements needed for optimal TDM practice and reported a recommendation. Both paper and electronic request forms were used by 77 out of 103 (75%) laboratories. A total of 69 out of 103 laboratories (67%) specified the type of sampling tube on their request form. Cystatin C was used for prediction of renal drug elimination by 24% (25 out of 103) of participants. Conclusions: Small number of laboratories implemented all elements needed for optimal TDM practice and report a recommendation on further dosing. Further efforts in education on optimal TDM practice as well as harmonization of service are desirable.